Effective treatment with a new protocol using tissue-type plasminogen activator thrombolysis for pump thrombosis with the HVAD device. Issue 8 (December 2018) - Schrage, Benedikt; Grahn, Hanno; Wagner, Florian M; Bernhardt, Alexander; Rybczynski, Meike; Blankenberg, Stefan; Reichenspurner, Hermann; Barten, Markus J
Background: Pump thrombosis is a major complication of the continuous flow left ventricular assist device. Pump exchange is seen as the therapeutic gold standard. In this study, we report on our experience with using tissue-type plasminogen activator thrombolysis for therapy of pump thrombosis. Methods: We report on our experience with treatment of continuous flow left ventricular assist device pump thrombosis with the HVAD using tissue-type plasminogen activator thrombolysis in nine patients with 16 thrombotic events. In all events we used a uniform treatment protocol. Results: All patients presented with a sufficient anticoagulation and had symptoms of heart failure. However, all patients were haemodynamically stable. Six of nine patients presented with a mean arterial pressure above 85 mm Hg and every patient presented with an infection. In all events we achieved short-term success with resolution of the pump thrombosis within a median time of nine hours. Three of nine patients developed recurrent pump thrombosis after >60 days. Besides one case of nonfatal intracranial haemorrhage and one case of minor bleeding, there were no adverse events. Conclusion: Our data indicates that using a uniform treatment protocol that builds on usage of tissue-type plasminogen activator thrombolysis might be an effective tool for treatment of continuous flow left ventricular assist device pump thrombosis in haemodynamically stable patients. Additionally, our data indicates that infection may be a potential trigger for pump thrombosis.